Effects of Charge Size on Slow Cook‐Off Characteristics of AP/HTPB Composite Propellant in Base Bleed Unit. Issue 4 (20th February 2018) - Li, Wenfeng; Yu, Yonggang; Ye, Rui
Abstract: To investigate the effects of charge size on the slow cook‐off characteristics of trilobite ammonium perchlorate (AP)/hydroxyl‐terminated polybutadiene (HTPB) composite propellant with slits, a cook‐off model of three‐dimensional base bleed unit is developed based on the two‐step decomposition reaction mechanism of AP/HTPB propellant at the external heating rates from 3.3 to 9 K/h. The charge length of AP/HTPB propellant is 72 mm with 43 mm to 53 mm in grain diameter, and the grain diameter is 43 mm with 72 mm to 90 mm in charge length, respectively. The results show that heating rate and charge size determine the ignition position of AP/HTPB propellant. The effects of charge size on the ignition position and cook‐off temperature are small at the heating rate of 3.3 K/h. As the heating rate increases to 4.6 K/h–6 K/h, with the grain diameter and charge length extending, the ignition position gradually moves from the inner wall to the surface near the slit, meanwhile the cook‐off temperature changes obviously. When the heating rate increases to 9 K/h, the ignition position of AP/HTPB propellant at different charge sizes all occurs on the outer interface between the propellant and slit, there is no obvious influence of different charge sizes on the ignition temperature of AP/HTPB propellant. Additionally, the law of ignition time of AP/HTPB propellant to charge size is the same at different heating rates. Abstract :